Gamma radiation effects on the conservation of onion ( Allium cepa) varieties of the São Francisco region, Pernambuco - Silva, Clemente J.G. Carneiro da; Sá Júnior, Júlio P.M. e; Silveira, Suêldo Vita da; Almeida, Lêucio Marques de; Godoy, Maria Oscarina; Dall’Olio, Attilio (Pesquisa Agropecuaria Brasileira, 2014)
Three varieties of onion (Allium cepa), "Amarela das Canárias", "Pera de Pernambuco" and Asgrow, cultivated in the São Francisco River region (Pernambuco), were irradiated at doses of 4, 8 and 12 krad, and were stored in Recife, at ambient temperature. In this preliminary experiment, rotting, loss of weight and sprouting of onions were observed during 120 days. After this period, the mean conservation index, expressed as the percent of the initial number of bulbs, reached, for the former two varieties, values of 92, 94 and 83% corresponding to doses of 12, 8 and 4 krad, respectively; whereas the Asgrow variety exhibited a mean conservation index of 3%. The non irradiated Asgrow samples were at that time wholly spoiled. No sprouting was observed in the irradiated samples and the total loss of weight was more marked in the non-irradiated bulbs. The statistical analysis of experimental data indicated that irradiation conservation effects were significant at the 0,1% level for the "Amarela das Canárias" and "Pera de Pernambuco" varieties, as verified through the F-test. Moreover, the analysis of variance displayed no significance for the interaction effects between doses and varieties, and the loss of weight through dehydration, followed up to 55 days did not show differences at the usual significance levels.